Design features of virtual reality foot reflexology stress therapy - Okere, Hector Chimeremeze; Abu Bakar, Juliana Aida; Che Mat, Ruzinoor (2018)
This paper presents the design of a VR for foot reflexology stress therapy application, VR-Foot-ReST. Reflexology therapy does natural healing to the body as there are reflex points at human feet and hands which correspond directly to each and every part of a human body. VR-Foot-ReST utilized its visual and oral interactivity coupled in a Head-Mounted-Display (HMD), with reflexology artifact (RA) for haptic interaction to provide foot reflexology therapy to its users. This article focuses on the design and development of the application on Android platform using prototyping development method. In developing the application, all the necessary multimodal requirements were gathered, compiled and verified before commencing the prototype development using a game engine. The prototype contains several visual and audio cues like text, ambience sounds, videos, and animations in English and Malay translations as well. The prototype has been proven to be useful and effective in helping users to combat stress and for relaxation using Virtual Reality. Conclusions and Future works were also discussed.